If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-x=4(5+3x)
We move all terms to the left:
2-x-(4(5+3x))=0
We add all the numbers together, and all the variables
-x-(4(3x+5))+2=0
We add all the numbers together, and all the variables
-1x-(4(3x+5))+2=0
We calculate terms in parentheses: -(4(3x+5)), so:We get rid of parentheses
4(3x+5)
We multiply parentheses
12x+20
Back to the equation:
-(12x+20)
-1x-12x-20+2=0
We add all the numbers together, and all the variables
-13x-18=0
We move all terms containing x to the left, all other terms to the right
-13x=18
x=18/-13
x=-1+5/13
| z/3+3=6 | | x+5-6=162 | | -|x-3.5|+4=0.25x-1 | | −3x+10−4x+1=32 | | -4v+(-17)=-57 | | 2-(x+7)=-5 | | 6(j+6)=72 | | 23=z-16 | | 8x-5=89 | | -17=-3z-(-22) | | fX17=34 | | -16x-48=10x+308 | | -4b-17=79 | | j-7=-1 | | 5y+2=-22 | | 20Xv=400 | | 8/9=40/h | | 12b-8=16+10b | | -6x-48=10x+308 | | 10x+2=4x=2 | | 14Xb=196 | | 12/16=9/n | | -5(4-x)=-75 | | 15-(-13)=2n | | 11x+4=6x+26 | | -5x-80-10x=90 | | 4x-1+7x+3=8x+4-3x+10 | | -16+13=9+3r | | F(-5)=-2x-12 | | 2x+18=-x+30 | | -9+n=13* | | 10x+15=6x+35 |